INTERUPSI PADA PERCAKAPAN PROSES PEMBELAJARAN BAHASA INGGRIS DI STIKES ST. ELISABETH SEMARANG - Maria Theresia Priyastuti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This research discusses the interruption that emerged in the conversation of English learning process in Stikes St. Elisabeth Semarang. The aims of the research are to describe the forms and the functions of interruption, of overlap and the adjacency pairs. The methods of the research are descriptive qualitative method, and unified method. The data were taken from conversation of English learning process that took place in Stikes St. Elisabeth Semarang. The data were analyzed by the researcher using the interruption theories from Beattie, Wardhaugh, Jefferson, etc. The result of the research shows that firstly, the forms of the interruption which are often found by the researcher in conversation of English learning process in Stikes St. Elisabeth Semarang, are overlap, smooth speaker-switch interruption, and simple interruption while the functions of the interruption are to ask question, to seek clarification, to correct and to complete the conversation. The forms of overlap often used, are transition onsets while the functions of overlap are often used to complete and to seek clarification. Secondly, the adjacency pairs are often used the forms of request followed explaining, and of question followed answer. Keywords: the interruption, the overlap, the adjacency pairs, the conversation of English learning process.